Regulation of the Rhizosphere Microenvironment by Arbuscular Mycorrhizal Fungi to Mitigate the Effects of Cadmium Contamination on Perennial Ryegrass (Lolium perenne L.) - Fan Yang; Jinji Han; Ruizhu Lin; Yuan Yin; Xiaoxia Deng; Yueming Li; Jixiang Lin; Jinghong Wang (Microorganisms)
Rhizosphere microorganisms are crucial for enhancing plant stress resistance. Current studies have shown that Arbuscular mycorrhizal fungi (AMF) can facilitate vegetation recovery in heavy metal-contaminated soils through interactions with rhizosphere microbiota. However, the mechanisms by which AMF influences rhizosphere microbiota and plant growth under cadmium (Cd) stress remain unclear. In this study, Lolium perenne L. was inoculated with AMF (Rhizophagus irregularis) and grown in soils supplemented with Cd (0 mg kg−1, Cd0; 100 mg kg−1, Cd100). Plant biomass, antioxidant enzyme activities, peroxide content, Cd uptake, and rhizosphere bacterial community composition were evaluated. AMF inoculation reduced Cd influx in aboveground tissues, enhanced nutrient availability in the rhizosphere, and mitigated Cd biotoxicity. Additionally, AMF inoculation improved the scavenging efficiency of reactive oxygen species and alleviated oxidative stress in L. perenne, thereby mitigating biomass reduction. Moreover, AMF treatment increased leaf and root biomass by 342.94% and 41.31%, respectively. Furthermore, under the same Cd concentration, AMF inoculation increased bacterial diversity (as measured by the Shannon index) and reduced bacterial enrichment (as indicated by the ACE index). AMF promoted the enrichment of certain bacterial genera (e.g., Proteobacteria and Actinobacteria) in the Cd100 group. These findings suggest that AMF regulated the composition of the rhizosphere bacterial community and promoted the growth of potentially beneficial microorganisms, thereby enhancing the resistance of L. perenne to Cd stress. Cd contamination in soil severely limits plant growth and threatens ecosystem stability, highlighting the need to understand how AMF and rhizosphere microbes can enhance Cd tolerance in L. perenne. Therefore, inoculating plants with AMF is a promising strategy for enhancing their adaptability to Cd-contaminated soils.